Comparison of liver fibrosis progression in HIV/HCV co-infected and HCV mono-infected patients by transient elastometry. (November 2014) - Mazzocato, Susanna; Orsetti, Elena; Gesuita, Rosaria; Piraccini, Francesca; Drenaggi, Davide; Barchiesi, Francesco
Abstract Monitoring of liver fibrosis (LF) is an essential tool for preventing liver-related complications in HIV/HCV co-infected patients. In this study, we compared LF progression by transient elastometry (TE) in 50 HIV/HCV co-infected and 115 HCV mono-infected patients followed in our institution between June 2006 and December 2011. Patients naive to interferon therapy and with at least two measurements of liver stiffness by TE were included. In all, 76% of HIV/HCV co-infected and 75% of HCV mono-infected patients remained in the same stage of LF over time. Conversely, 19% and 15% of HIV/HCV co-infected and HCV mono-infected subjects, respectively, had progression to advanced LF (≥ F3). Our study found a similar proportion of HIV/HCV co-infected and HCV mono-infected patients that developed an advanced LF during the follow-up time considered. Alcohol abuse was the only factor significantly associated with the progression as evidenced by multiple quantile regression analysis.